In situ melanoma of oral cavity: Diagnosis and treatment of a rare entity - Cardoso, Diovana de Melo [UNESP]; Bastos, Daniela Brito [UNESP]; dos Santos, Daniela Micheline [UNESP]; Conrado-Neto, Sebastião [UNESP]; Collado, Francisco Urbano [UNESP]; Crivelini, Marcelo Macedo [UNESP]; Xavier-Júnior, José Cândido Caldeira; Biasoli, Éder Ricardo [UNESP]; Miyahara, Glauco Issamu [UNESP]; Bernabé, Daniel Galera [UNESP] (Elsevier, 2021)
Oral melanoma is an extremely aggressive and rare tumor. Commonly, oral melanomas are diagnosed as invasive tumors, which considerably reduces the chances of cure. In situ oral melanomas being exceedingly rare, which makes its clinicopathological and prognostic characteristics poorly known. Herein, we report a case of 67-year-old non-white woman with a large black patch on the maxillary alveolar mucosa. A biopsy was made and microscopical analysis revealed moderate atypical junctional melanocytic. Tumor cells were positive for S100 (Polyclonal), Melan-A (Clone A103) and Melanosome (HMB-45). The diagnosis of in situ oral melanoma was made and the patient was treated surgically with partial maxillectomy and rehabilitated with obturator prosthesis. Although extremely rare in situ melanomas should be considered in the differential diagnosis of non-invasive pigmented lesions of the oral mucosa.
Keywords: Cancer; Early diagnosis; Head and neck tumor; Melanoma; Oral cavity; Oral health; Oral melanoma